IMPLEMENTASI METODE PREVIEW QUESTION READ REFLECT RECITE REVIEW DALAM MENINGKATKAN KEMAMPUAN MEMBACA SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV DI SEKOLAH DASAR NEGERI 04 PERIGI LIMUS TAHUN PELAJARAN 2023-2024 - Sherin Novisyah; Eliyah, Asyruni Multahada (ADISAM PUBLISHER, 2024)
The aim of this research is to reveal: 1) Describe the teacher's planning for using the PQ4R method to improve the reading skills of class IV students at SDN 04 Perigi Limus for the 2023-2024 school year?; 2) Describe how the PQ4R method can improve the reading ability of students in class IV at SDN 04 Perigi Limus in the 2023-2024 school year?; 3) Describe students' reading abilities after applying the PQ4R method in class IV Indonesian language lessons at SDN 04 Perigi Limus for the 2023-2024 school year? This research uses a qualitative approach and a type of classroom action research. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data collection, data reduction, data display and conclusions. The research results show that; 1) The planning made by the teacher uses PQ4R (Preview, Question, Read, Reflect, Recite and Review) as in general learning, such as the activity steps in the introduction, core and closing activities. Planning is designed for two cycles. The second cycle is the result of reflection with changes to the preparation of learning materials using the demonstration method. 2) Implementation of learning according to the one week reflection learning plan for PQ4R (Preview, Question, Read, Reflect, Recite and Review) with reading activities from demonstrations and listening to explanations of PQ4R. Implementation of learning in cycles one and two as planned in cycle one using the PQ4R method by reading and analyzing stories in books. Based on the results of reflection by adding activities other than reading books by observing and listening to videos displayed on the projector. 3) Based on the results of the classroom action research that has been presented, the research can be concluded as follows: The use of the PQ4R method can improve students' reading skills in the subject Indonesian class IV. With the complete reading ability of students in cycle I amounting to 67,85% and in cycle II amounting to 84,52%. So, from cycle I to cycle II students' reading ability increased by 16.67%